A formação docente na área de Recomposição e Recuperação Contínua de Aprendizagem com foco na alfabetização e no letramento - Rocha, Rosineide de Andrade (Universidade Federal de São Carlos, 2026)
Faced with the challenges inherent in improving the quality of Brazilian education, those related to raising the level of student performance in the context of literacy and reading comprehension emerge. Whether in literacy cycle classes (1st and 2nd year of Elementary School) or in Remedial/Reconstruction of Learning classes, teachers need to be supported and subsidized to build meaningful work. The research question guiding this study is: what knowledge is essential to the Knowledge Base of a literacy teacher working in the context of Learning Recovery/Reconstruction and in regular classes of the initial years of Elementary School? The objective is to analyze the teacher learning mobilized/constructed within the context of a training proposal in the area of Continuous Learning Recovery/Reconstruction, focusing on literacy and reading comprehension, aiming at a possible outlining of the literacy teacher’s Knowledge Base and, consequently, their professional development. The approach used in this study is qualitative research, especially collaborative research through an intervention, based on the ideas of Ibiapina (2008) and Mizukami (2000; 2010). The training action involved the planning and implementation of a hybrid training proposal in the area of Continuous Learning Recovery/Reconstruction, focusing on literacy and reading comprehension. This training action began in the first semester of 2024, with a workload of 120 hours and certification. This training was conducted by the UFSCar extension program and made available to teachers working in the Municipal Education System of Bebedouro (SP), with 38 teachers completing the activity. Data sources included the researcher’s logbook; questionnaires; narratives (training memoir, teaching cases, report of pedagogical practices); and a conversation network. Data analysis employed the content categorization technique of Bardin (2016) and Franco (2018), except for the analysis of narratives. The research analysis was structured and unfolded around three key ideas: the research subjects; collaborative processes triggered to expand the Knowledge Base of literacy teachers; and indicators of theoretical-practical contributions to the Knowledge Base of literacy teachers. The results, through the participants’ discourses, show that, especially in the collaborative proposals outlined, new conceptions, theoretical/methodological resignifications, and significant reflections emerged about the Pedagogical Content Knowledge of the literacy teacher, working in regular classrooms or in the context of Continuous Learning Reconstruction/Recovery with a focus on literacy and reading comprehension. Based on the teachers’ observations, it was possible to construct a suggested training guide entitled “Essential Elements of the Pedagogical Content Knowledge (PCK) of the teacher to teach literacy/reading comprehension from the perspective of the BNCC”, in addition to guidelines for adjusting this guide to the need to recover/compose learning. Such evidence may contribute to effectively improving teacher training (initial and continuing) and teaching and learning in classrooms, as well as to fostering public policies or teacher training programs in this area.
Teacher training in the area of ​​Continuous Learning Recovery and Rehabilitation with a focus on literacy and reading comprehension
Keywords: Formação de professores; Recomposição e recuperação de aprendizagem; Alfabetização e letramento; Base de conhecimentos; Desenvolvimento profissional; Anos iniciais do ensino fundamental.; Teacher training; Learning reconstruction and recovery; Literacy and reading comprehension; Knowledge base; Professional development; Early years of elementary school.; CIENCIAS HUMANAS::EDUCACAO; 4. Educação de Qualidade